Hydrogen recovery from the purge stream of an HDA process using the concept of Mass Exchange Networks - Fischer, Carlos Daniel (2013)
In this paper we use the concept of Mass Exchange Networks to design the hydrogen recovery from the purge stream of an HDA Process by implementing a recently proposed counter current gas permeation equipment to exchange hydrogen between the purge and the toluene feed to the process. This design would correspond to the final design refinement step in the Douglas and hierarchical process design procedure, proposed by Fischer and Iribarren. The goal of this design is recovering part of the hydrogen available in the purge stream, and results in a process alternative different from other flow sheet recently proposed by Bouton and Luyben, also resorting to gas permeation membrane units, but in a traditional arrangement. Two different types of available zeolite ceramic membranes were studied, of different permeability and selectivity. The here proposed mass exchange design recovers a similar amount of hydrogen as the process alternative proposed by Bouton and Luyben who use a less expensive type of polymeric membrane, but need a compressor to recycle the permeate stream because they use transmembrane pressure as the driving force. The here proposed design at actual cost of zeolite membranes allows an 153.9% increase of the Net Annual Savings with respect to the pressure driven membrane system when using the less selective ceramic membrane, while this figure descents to a 32.61% when using the most selective (which is also the most expensive alternative).